The Lyapunov spectra of quantum thermalisation - A. Hallam (Nature Portfolio, 2019)
The relationship between thermalisation of classical system via dynamical chaos and the one of closed quantum systems is far from totally understood. Here, the authors shed light on this connection by projecting quantum dynamics to classical chaotic ones and determining its Lyapunov spectrum.